The effects of feeding a high concentrate ration containing 25% ground beef manure to fattening heifers in concrete and soil-surfaced lots - C.L. Drake; L.I. Smart; E.F. Smith; R.I. Lipper (Kansas Agricultural Experiment Station Research Reports, 1968)
This is a cooperative project with the Department of Agricultural Engineering to study surface runoff, in addition to animal performance. Twenty Hereford heifers were randomly allotted to four equal sized lots: 2 surfaced with concrete and 2 with soil. Self-feeders in soil-surfaced lots have concrete aprons.
Keywords: Cattlemen' s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Ground beef; Concrete vs. soil-surfaced lots; High energy ration